The Degree of Implementation of Blue Ocean Strategy And its Relationship with Financial Performance - Herzallah, Ahmad; Alghwanma, Moayad (The Arab Journal of Administration, 2021)
The study was designed to identify the degree of implementation of Blue Ocean strategy and its relationship with the financial performance in the Palestinian food industry companies. The study used a descriptive approach. A questionnaire was designed which included 32 items distributed on four dimensions. The database of the Palestinian Food Industries Union, which contains about 117 companies, was used to identify organizations appropriate for this study. A total of 90 structured questionnaires with closed questions were sent to companies. Ultimately, 80 questionnaires were completed and returned, of which 5 were excluded because they were incomplete, leaving 75 usable questionnaires. Results derived from this study showed that the overall score for the implementation of Blue Ocean strategy in the Palestinian industrial food companies was high with a total average of 4.30 and to a large extent. The arithmetic average of the total score of the financial performance was 4.08. A positive relationship was found between the degree of application of the combined Blue Ocean strategy and its dimensions and the financial performance of the food industry companies. Furthermore, there were no significant differences at the level of statistical significance (a≤0.05) in respondents’ responses to the degree of implementation of the Blue Ocean strategy according to company age, but there is a difference between companies according to sales volumes.